Analisis Layanan Prima dalam Penanganan Keluhan Pelanggan di PT XYZ: Evaluasi Efektivitas, Dampak terhadap Kepuasan, dan Strategi Peningkatan Kinerja Layanan - Gracia Irena Saputri; Puji Wahono; Suherdi Suherdi (STIKes Ibnu Sina Ajibarang, 2025)
The increase in customer complaints in e-commerce services requires an effective excellent service strategy to maintain customer trust and loyalty. This study aims to analyze the complaint handling strategy at PT. XYZ. This study uses a descriptive qualitative method with in-depth interview techniques on four respondents who have different roles in customer service management. The results show that the most common complaints include product discrepancies, delivery delays, and slow refund processes. The main challenges include limitations in digital systems, interdepartmental coordination, and limited human resources. This study suggests optimizing customer service technology, strengthening internal coordination, and enhancing human resources to support 24/7 service and reinforce the company's image. Product discrepancies often arise from miscommunication between the sales and warehouse departments, leading to customers receiving products that do not match their expectations or the descriptions provided. Delivery delays are a common frustration, particularly during high-demand periods, affecting customer satisfaction and leading to negative reviews. Additionally, slow refund processes create frustration for customers, especially when dealing with returns or faulty products. These delays hinder the company's ability to provide excellent service and detract from the customer experience. One of the primary challenges identified in the study is the limitation in the digital systems used for customer service management. PT XYZ’s current system is not fully optimized to handle high volumes of complaints, leading to delays in responses and resolutions. Interdepartmental coordination is also a significant issue, as different departments such as logistics, sales, and customer service often operate in silos, making it difficult to resolve customer issues promptly.